2014
DOI: 10.1105/tpc.113.121723
|View full text |Cite
|
Sign up to set email alerts
|

Kinesins Have a Dual Function in Organizing Microtubules during Both Tip Growth and Cytokinesis in Physcomitrella patens

Abstract: ORCID IDs: 0000-0002-3996-0549 (Y.H.); 0000-0001-6027-1919 (J.H.D.) Microtubules (MTs) play a crucial role in the anisotropic deposition of cell wall material, thereby affecting the direction of growth. A wide range of tip-growing cells display highly polarized cell growth, and MTs have been implicated in regulating directionality and expansion. However, the molecular machinery underlying MT dynamics in tip-growing plant cells remains unclear. Here, we show that highly dynamic MT bundles form cyclically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 40 publications
5
63
0
Order By: Relevance
“…In support of this hypothesis, Hiwatashi et al (2014) discovered that two microtubule-based motors, KINESIN FOR IN-TERDIGITATED MICROTUBULES1a (KIND1a) and KIND1b, regulate microtubule organization and protonemal growth. The kind1a,b knockout plants exhibit protonemata that do not grow straight but still have tipward-growing cytoplasmic microtubules.…”
Section: Microtubule Cytoskeletonmentioning
confidence: 95%
See 1 more Smart Citation
“…In support of this hypothesis, Hiwatashi et al (2014) discovered that two microtubule-based motors, KINESIN FOR IN-TERDIGITATED MICROTUBULES1a (KIND1a) and KIND1b, regulate microtubule organization and protonemal growth. The kind1a,b knockout plants exhibit protonemata that do not grow straight but still have tipward-growing cytoplasmic microtubules.…”
Section: Microtubule Cytoskeletonmentioning
confidence: 95%
“…In moss protonemata, there are also two populations of microtubules: cytoplasmic and cortical. In the apical cell, the polarity of cytoplasmic microtubules between the nucleus and the cell apex is tipward, with an apical focus of microtubule plus ends (Hiwatashi et al, 2014). In contrast, the cortical microtubule array consists of shorter microtubules that lack polarity (Burkart et al, 2015;Nakaoka et al, 2015).…”
Section: Microtubule Cytoskeletonmentioning
confidence: 99%
“…In this regard, the branching nucleation in this system might be a variation of cytoplasmic nucleation; cytoplasmic-like nucleation occasionally occurs on MTs, rather than in the cytoplasm. Longitudinal alignment of endoplasmic MTs might occur after MT nucleation, for example, through MT transport ( Figure 2B) or cross-linking (Doonan et al, 1985;Hiwatashi et al, 2014). g-Tubulin was detected at the majority of the branching sites.…”
Section: Mechanism Of Branching Nucleationmentioning
confidence: 99%
“…In P. patens, germinated spores develop into a tissue called "protonemata," in which two types of cells, chloronemata and caulonemata, have been identified. Immunofluorescence microscopy and live imaging of MTs have shown that these cells do not form conventional cortical MT arrays but rather form "endoplasmic MTs" that run throughout the cytoplasm (Doonan et al, 1985;Hiwatashi et al, 2014). Endoplasmic MTs play a critical role in protonemal cell growth (Doonan et al, 1985(Doonan et al, , 1988, but how they are generated is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The KINID1a and KINID1b kinesins in these cells are responsible for the bundling of microtubule plus ends. Loss of both these kinesins leads to reduced microtubule bundling and aberrant tip growth (Hiwatashi et al, 2014) The ARMADILLO-REPEAT KINESIN1 (ARK1), originally named MORPHOGENESIS OF ROOT HAIR2 (MRH2) (Jones et al, 2006), is thought to participate in microtubule dynamics. Because ARK1 is an uncharacterized kinesin belonging to an ungrouped plantspecific family of kinesins, its function cannot be predicted based on phylogeny (Reddy and Day, 2011;Zhu and Dixit, 2012).…”
Section: Introductionmentioning
confidence: 99%